Drug release kinetics and transport mechanisms of doxorubicin from core-shell delivery systems - Kocabay, Ozlem Gokce; Ismail, Osman (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2025)
In the current research drug release kinetics and transport mechanisms of doxorubicin (DOX) from DOX, DOX/valspodar (PSC 833) and DOX/D-alpha- tocopheryl polyethylene glycol 1000 succinate (TPGS 1000) loaded polymeric micelle (PM) delivery systems were studied. Mathematical modeling has shown that the best suitability for release at pH 5.0 medium (R2 > 0.98) is provided by Korsmeyer-Peppas model and drug release kinetics are both anomalous transport (non-Fickian) and Super case II transport. The drug release was considered to fits in both the Korsmeyer-Peppas and Weibull models for DOX release from DOX-PM, DOX/PSC 833-PM, DOX/TPGS 1000-PM at pH 6.5 and pH 7.4 medium.
Keywords: diffusion; dissolution; drug release mechanism; drug release modeling; erosion; swelling; TPGS; Science & Technology - Other Topics